Patrzenie jako źródło cierpień (z rzymskich dziejów pewnego motywu literackiego) - Pigoń , Jakub (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The paper examines a number of Roman literary texts (by Ennius, Cicero, Vergil, Ovid, Seneca the Younger, Lucan, Tacitus, Jerome, etc.) in which viewing is connected with mental or emotional suffering. Usually, the emphasis is laid on a character’s viewing of some dramatic events – a close relative’s death, for example – and on his or her emotional response to what is being seen. In some works, especially in consolatory contexts, someone’s premature death is presented as advantageous because the dead person is now spared the necessity of viewing misfortunes which the living have to witness. Also, people may be compelled (e.g. by an emperor) to watch evil things; in such a situation they are usually viewers and objects of viewing at the same time, since their gestures and facial expression are carefully observed.